(3fXQjI GdEbJUGO Gdcdj (B:s (3eONd QjGVj ddSjGSI GdeGdjI hGdfbOjI (B/s - (3GdfGbI, CMeO CHh GdaJhM Ydjs ((3GdEScfOQjI(B: s (3ecJHI heWHYI GdETYGY GdafjI(B, s, 2002)
(3MSGHGJ GdONd Gdbhej(B- (3JhGRf LGfH GdWdH aj GdEbJUGO Gdbhej(B- (3JMOjO eSJhi GdONd hSYQ GdaGFOI(B- (3ebOeI aj GdSjGSI GdeGdjI aj Xd KHGJ GdeSJhi GdYGe ddCSYGQ(B- (3efMi GdWdH Gdcdj dEfJGL Gdcdj GdeWdhH heSJhi GdCSYGQ(B- (3JMdjd GdWdH Gdcdj hGdYQV Gdcdj Hjf hLgI fXQ GdfbOjjf hGdcjfRjjf(B- (3GdfbhO hGdJVNes
Keywords: (3GdCShGbs; (3GdEbJUGO Gdcdjs; (3GdEbJUGO(B- (3fXQjGJs